A kinematic comparison of deep water running and overground running in endurance runners - Kilding, A. E.; Scott, M. A.; Mullineaux, D. R. (The Journal of Strength and Conditioning Research, 2007)
Deep water running (DWR) is commonly used as a rehabilitative tool or as a running specific cross-training modality. However, because little is known about the biomechanical specificity of this training, the aim of this study was to compare the leg kinematics of DWR vs. overground running (OGR). Five endurance runners' leg actions in the sagittal plane were filmed in 2 dimensions in DWR and OGR at slow (72 cycles/min) and fast (92 cycles/min) frequencies to measure hip and knee angles. Hip-knee angle-angle diagrams were quantified using cross-correlations (r). Leg motion was different between DWR and OGR both kinematically (e.g., hip maximum flexion angle, slow frequency: DWR = 92 +/- 20° OGR = 49 +/- 10[degrees] p < 0.05) and in coordination (e.g., slow frequency: DWR, r = -0.94, lag = -1%; OGR, r = 0.87, lag = 22%). The time lag indicates that the hip and knee flex and extend together in DWR, whereas the hip moves before the knee during OGR. Stride frequency had an effect on OGR but not on DWR. The apparent differences between DWR and OGR are likely to affect muscle recruitment patterns and this could be problematic for athletes with hip and knee injuries. Because the negative effects of DWR as a rehabilitative tool are not known, gradual familiarization to DWR prior to a prescribed DWR rehabilitation or intense fitness maintenance program is recommended to offset any adverse affects.